Isolation, identification and characterization of rumen bacteria and estimation of their fibre degradable enzymes in yak (Bos grunniens) - MEDHI, D; ALI, EYASHIN; CHOUDHURY, L C; BARUAH, K K; A, SANTRA; DUBEY, SWATI; AGARWAL, PAYAL; CHAKRAVARTY, P (The Indian Journal of Animal Sciences, 2022)
To utilize the plant nutrients efficiently, rumen microbes play a great role in the livestock, acting as a source of energy. Like other ruminants, the yak rumen harbours different microorganisms that are responsible for bioconversion of nutrients into a source of energy for the animals. The samples of rumen liquor were collected from the yak (Bos grunniens) rumen. The specific media was made to culture the rumen microbes and isolated the pure culture with serial dilution. The pure colony was identified with the help of 16S ribosomal gene sequencing. The enzyme activity of the isolates was observed by estimating the enzymes like Carboxymethyl Cellulase (CMCase) and Avicilase. The isolates were identified with the help of specific primer (Fibrobactor succinogen) and characterized which were closely related to Bacteroides pyogenes and Ruminococcus species. The study indicates diverse group of rumen bacterial population in yak rumen. Fibrobactor succinogen, Ruminococcus and Bacteroides species take potential roles as source of microbial enzyme for degradation of feed and fodder in yaks.